Viruses of microorganisms (Caister Academic Press, 2018)
In this multi-authored volume, international experts review the genomics, ecology, comparative biology and biotechnological applications of these fascinating viruses. Chapters have extensive reference sections that should encourage readers to pursue each subject in greater detail. This unique reference volume is a must-read for everyone working with VoMs, from the PhD student to the experienced scientist, in academia, the pharmaceutical or biotechnology industries and working in clinical environments.